2012
DOI: 10.1002/eji.201141965
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 modulates IL‐8 expression through formation of a multiprotein enhanceosome in human colonic epithelial cells

Abstract: . Since ICER lacks the transactivation domain, it functions as a transcription repressor as opposed to CREB. PGE 2 coupling through EP2/4 receptors can therefore acts in an opposing manner to either decrease (EP2) or promote IL-8 expression by recruiting CREB-binding protein (CBP) (EP4), which formed a multiprotein IL-8 enhanceosome. A novel half CRE (167CRE) and a composite NFAT1-AP1-like site in the IL-8 promoter participated in binding and complex formation as confirmed by mutagenesis and expression studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Under normal condition, this site remains methylated, while upon arsenic induced demethylation, it may lead to IL-8 expression. Encompassing the À168 site is the binding site for CAAT/enhancer biding protein (C/EBP) transcription factor (NsiteMSoftBerry) and cAMP response element binding protein (CREB) (Srivastava et al, 2012). Srivastava et al (2012) had described the role of À168 site by using site directed mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under normal condition, this site remains methylated, while upon arsenic induced demethylation, it may lead to IL-8 expression. Encompassing the À168 site is the binding site for CAAT/enhancer biding protein (C/EBP) transcription factor (NsiteMSoftBerry) and cAMP response element binding protein (CREB) (Srivastava et al, 2012). Srivastava et al (2012) had described the role of À168 site by using site directed mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Encompassing the À168 site is the binding site for CAAT/enhancer biding protein (C/EBP) transcription factor (NsiteMSoftBerry) and cAMP response element binding protein (CREB) (Srivastava et al, 2012). Srivastava et al (2012) had described the role of À168 site by using site directed mutagenesis. Mutation at À168 site was found to decrease the expression of IL-8 suggesting its crucial role.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, cAMP-response element-binding protein (CREB), a transcription factor, is one of the major downstream targets of PKA, which controls cellular functions via synthesis of a wide variety of proteins (Shaywitz and Greenberg, 1999). EP4-mediated CREB activation was reported in colon epithelial cells (Srivastava et al, 2012), dorsal root ganglion neurons (Cruz Duarte et al, 2012), Leydig tumor cells (Sirianni et al, 2009), and breast cancer cells (Subbaramaiah et al, 2008). Other signaling pathways in addition to CREB are activated via PKA.…”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…Srivastava et al (2012) examined the mechanisms of differential regulation of IL-8 production by EP4 and demonstrated that PGE 2 -EP4 signaling activated CREB through both the PKA and PI3K pathways. Interestingly, they also demonstrated that EP2 activated the transcription factor-inducible cAMP early repressor (Srivastava et al, 2012). Because inducible cAMP early repressor lacks the transactivation domain, it functions as a transcription repressor, unlike CREB.…”
Section: Other Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation